Energy Efficiency Standards and Labels for Cold Appliances in Jordan - Alfattah, Alwiyah Abd; Sakhrieh, Ahmad; Al-Ghandoor, Ahmed (International Journal of Energy Economics and Policy, 2017)
In the last few years, Jordan has experienced an expansion in the number of electrical appliances. In order to reduce energy consumption in the residential sector, Jordanhas to consider implementing minimum energy efficiency standards (MEES) for electrical appliances in the coming years. This study provides background on the benefits of, and steps needed to support introduction of Energy Efficiency Standards and Labeling in Jordan. Furthermore, this study attempts to predict the amount of energy that will be saved in the residential sector by implementing MEES for the cold electrical appliances (refrigerators and freezers). This study concentrates on cold electrical appliances because it was found that cold appliances are about 32.7% of total household electrical energy consumption in Jordan. Four scenarios for replacing the old appliances have been suggested and analyzed. It was found that the net saving from 2011-2020 will be approximately 4451.17 GWh. The associated CO2 emission reduction during the 10 years is expected to reach 2221 (1000 ton). In addition, the reduction of customer bills will reach 320 million JD based on the worst scenario. Keywords: energy efficiency; standard; appliances; Jordan. JEL Classification: Q4